Experimental facility for investigation of lightning performance of distribution lines. - Nakada, K. (IEEE Transactions on power delivery)
In order to clarify the lightning performance of a distribution line, test distribution lines and a test tower were constructed at the Mikuni Testing Center of Hokuriku Electric Power Company in 1999. Using these facilities, the authors observed transient voltages and current distributions due to direct strokes of natural lightning. Based on this data, we have clarified the following points: (1) calculated voltages and currents using the EMTP agree with the experimental results fairly well; and (2) for lightning currents of long durations, however, the reduction of voltages across arresters by energy absorption should be taken into consideration.